Pelatihan penyusunan Lembar Kegiatan Peserta Didik (LKPD) berbasis inquiry - Nurhayati Nurhayati; Bunga Dara Amin; Nurhilaliyah Nurhilaliyah (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Since the 2013 curriculum was set, the burden on teachers has increased. Learning approaches and models and their integration in learning tools are difficult obligations for a teacher. So it is not surprising that teachers often make mistakes, especially in the form of Student Worksheets that must be adapted to the learning model used. Therefore, the implementation of this Community Partnership Service provides training to teachers, so that they can compile the Educator Worksheet, specifically inquiry-based, which is predicted to be most appropriate in the current curriculum transition situation. The results of Community Partnership Service show that teachers already have the ability to compile Student Worksheets based on Student Worksheets. The teacher is also able to compile similar Student Worksheets for all basic competencies that are possible through proper curriculum analysis. This provision is very useful for teachers, it can even be applied for the preparation of Student Worksheets based on other learning models.